2022
DOI: 10.1108/mmms-05-2022-0080
|View full text |Cite
|
Sign up to set email alerts
|

Wire EDM cutting of Inconel 718 nickel-based superalloy: kerf and MRR analysis

Abstract: PurposeInconel 718 (IN718) is a high-performance nickel-based superalloy with high oxidation-corrosion-temperature resistance, high strength (tensile, fatigue, creep and rupture), durability, toughness, hardness and dimensional stability, which is difficult to machine with traditional fabrication methods. To overcome these difficulties, wire electrical discharge machining (WEDM), one of the modern manufacturing methods, is used.Design/methodology/approachMain performance criteria in WEDM; material removal rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…After determining the drilling parameters and levels, the appropriate orthogonal design (L18) and the quality characteristics, the relationships between the control factors/drilling parameters and the quality characteristics were realized by applying the steps of the TEDM as follows (Figure 3). 14,35,40–44 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After determining the drilling parameters and levels, the appropriate orthogonal design (L18) and the quality characteristics, the relationships between the control factors/drilling parameters and the quality characteristics were realized by applying the steps of the TEDM as follows (Figure 3). 14,35,40–44 …”
Section: Methodsmentioning
confidence: 99%
“…After determining the drilling parameters and levels, the appropriate orthogonal design (L18) and the quality characteristics, the relationships between the control factors/drilling parameters and the quality characteristics were realized by applying the steps of the TEDM as follows (Figure 3). 14,35,[40][41][42][43][44] The TEDM can only optimize a single response and cannot optimize more than one response at the same time. Most of the problems that arise in industrial applications are multi-criteria in nature, so that making a decision based on only one evaluation criterion often makes no sense.…”
Section: Optimization and Modelingmentioning
confidence: 99%
“…They found that with the decrease in wire electrode diameter, cutting precision increased, and wire and workpiece waste decreased, resulting in lower environmental impacts, reduction in craters on the machined surfaces, reduction in microhardness change, and reduction in recast layer thickness value. Karataş [27] machined Inconel 718 alloy via the WEDM method, considering changes in MRR and kerf by process parameters using gray relational analysis (GRA) and analysis of variance (ANOVA) methods. It was concluded that wire tension significantly affected the MRR while the effect of dielectric fluid pressure was insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…They found that with the decrease in wire electrode diameter, cutting precision increased, and wire and workpiece waste decreased, resulting in lower environmental impacts, reduction in craters on the machined surfaces, reduction in microhardness change, and reduction in recast layer thickness value. Karataş [25] machined Inconel 718 alloy via the WEDM method considering changes in MRR and kerf by process parameters using Gray Relational Analysis (GRA) and Analysis of variance (ANOVA) methods. It was concluded that wire tension signi cantly affected the MRR while the effect of dielectric uid pressure was insigni cant.…”
Section: Introductionmentioning
confidence: 99%